An Inquiry Into The Determinants of Research Sector Productivity - Jendi,Nicolas (2023)
This paper constitutes an inquiry into the determinants of research sector productivity. Three variables thought to be relevant in determining the productivity of the research sector of an economy are proposed and examined on the basis of Paul Romer’s (1990) model of endogenous economic growth. The productivity of the research sector in the aforementioned model of economic growth is conceived to be a function of the three variables proposed in this paper. These three are openness in the research sector, market conditions for research, and access to the stock of knowledge. The aim of the paper is to inquire into the character of these variables and their influence on the productivity of the research sector.
Keywords: Innovation; Endogenous Growth; R&D; Romer model